Karakteristik Kemasan Nampan Berbasis Pati Termoplastis, Glukomanan Termoplastis Dan Poliasam Laktat Dalam Variasi Suhu Dan Waktu Pencetakan - Aimar, Ilhan Maulana; Harsujuwono, Bambang Admadi; Antara, Nyoman Semadi; Hartiati, Amna; Suhartini, Sri (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
Biothermoplastic composites are mixtures of two or more polymers from biological materials with other materials that can melt when heated and harden again when cooled. The formation of packaging trays from biothermoplastic composites is greatly influenced by many factors including temperature and molding time. This study aims to determine the effect of molding temperature and time on the characteristics of tray packaging from thermoplastic starch, thermoplastic glucomannan and latic polyacud biothermoplastic composite raw materials. This study used a 2-factor with 9 treatments, each treatment repeated as many as 2. The first factor is temperature (S) which consists of 3 temperature levels 130  (S1), 145  (S2), 160  (S3). The second factor is time (W) which consists of 3 levels of 30 seconds (W1), 45 seconds (W2), 60 seconds (W3). The results showed that temperature and molding time significantly affected the tensile strength, elongation at break, elasticity, thickness development, density, biodegradation time and leakage test of TPS/TPG/PLA biothermoplastic composite tray packaging. The best tray packaging was obtained at molding with a temperature of 160 ℃ and a time of 45 seconds with a tensile strength value of 42.20  MPa, elongation at break value of 0.70%, modulus young of 6, 12 GPa, swelling of 0.47%, density of 1.31 g/cm3, biodegradation time of 24.00 days and leakage test (not leak). However, modulus young, elongation at break and density have not met the standards set.